THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK DISCIPLINE THROUGH WORK INVOLVEMENT AS AN INTERVENING VARIABLE IN IMPROVING EMPLOYEE PERFORMANCE AT THE MEDAN HELVETIA SUB-DISTRICT OFFICE - Hanifah; Kholilul Kholik; Darmilisani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of Organizational Culture and Work Discipline on Employee Performance with Work Engagement as a mediating variable at the Medan Helvetia Sub-District Office. This research employs a quantitative approach using the Partial Least Square (PLS) method to examine the relationships among variables. Data were collected through questionnaires distributed to employees of the Medan Helvetia Sub-District Office. The results indicate that Organizational Culture has a positive and significant effect on Work Engagement but does not have a direct effect on Employee Performance. Work Discipline has a positive and significant effect on both Work Engagement and Employee Performance. Furthermore, the results show that Organizational Culture positively and significantly affects Work Engagement with an original sample value of 0.501 and a p-value of 0.000. Organizational Culture has a positive but not significant effect on Employee Performance with an original sample value of 0.120 and a p-value of 0.214. Work Discipline positively and significantly affects Work Engagement with an original sample value of 0.472 and a p-value of 0.000, and it also positively and significantly affects Employee Performance with an original sample value of 0.354 and a p-value of 0.000. Work Engagement positively and significantly affects Employee Performance with an original sample value of 0.479 and a p-value of 0.001. Organizational Culture positively and significantly influences Employee Performance through Work Engagement with an original sample value of 0.240 and a p-value of 0.005, while Work Discipline positively and significantly influences Employee Performance through Work Engagement with an original sample value of 0.226 and a p-value of 0.002.